Clusters as an instrument to bridge institutional voids in transition economies Lessons learned from Southeast Europe - Schrammel, Tine.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2014)
Transition economies, such as the countries in Southeast Europe, face an expeditious institutional transition from a centrally planned to a market economy. The state withdraws from its monitoring function, which results in institutional voids that affect the economy in general and small and medium sized enterprises (SMEs) in specific. With a qualitative case study approach Tine Schrammel develops a scheme to detect institutional voids as one source of competitive disadvantages of SMEs in transition economies. In a second step she demonstrates that specific cluster services bridge institutional voids and improve the competitive position of SMEs in environments of institutional voids. The findings add to the understanding of institutional voids and to the role of clusters in transition economies. Contents Environments of institutional voids Case studies from Southeast Europe Cluster support Target Groups Lecturers and students of business administration with focus on international management, regional development and development cooperation Cluster Managers, Policy Makers, and SMEs from and entering into Southeast Europe The Author Tine Schrammel received her PhD from the University of Passau, where she was affiliated with the Chair of International Management (Prof. Dr. Carola Jungwirth). She worked for development cooperation in Southeast Europe.
Environments of institutional voids -- Case studies from Southeast Europe -- Cluster support.
Keywords: Business; Small business; Globalization; Markets; Economic policy; Business and Management; Small Business; Emerging Markets/Globalization.; Economic Policy; Electronic books